What Is a Formulary, Anyway? Part 2 - Richard H. Parrish (MDPI AG, 2018)
This paper is a continuation of the first paper on drug formularies. It details the various types of formularies, and speculates on the future of formularies as an instrument for improving rational drug therapy.